A Review on Emerging Applications of Artificial Intelligence in Civil Engineering - P. Krishna Prasanna, T. Sujatha, P. Rajasulochana, K. Srinivasu, G. Sheena Ecclesia (Mathematical Statistician and Engineering Applications, 2023)
Civil engineering began with solving problems that were faced by society. Initially, it focused on the implementation of physical and mathematical concepts to solve the problems technically and create engineering solutions. The ancient, medieval, and modern history of civil engineering, implementing new ideas, techniques, and tools to solve real-time problems through AI. These new techniques have created an impact on civil engineering. AI attempts to construct and make operations reasonably simple and precise. Its Trailblazing modeling techniques help crack many complex problems and assist as an analytical tool for diagnosing the results. Machine learning is an application of AI, where a computer uses intelligence to act as a human to accomplish tasks during the process of mathematical models of data that enables a computer to learn and perform on its own experience without any instructions. However, there are no broad appraisals or explanations regarding their applications, so this study focuses on the ethical aspects of their applications, like their predominant role in enhancing the construction industry, geotechnical, watershed management, and transportation fields summarizes it hallow side.